Checklist of Deuteromycetous fungi of Bangladesh – III (Bioresearch Communications, 2024)
Sixly two species of anamorphic fungi under 17 genera belonging to the  Form family  Sphaeropsidaceae and Melanchoniaaece in Bangladesh from 1952 till date are enlisted in this account. The alphabetical checklist of the genera is provided herewith. Further updates will be added in the subsequent versions of the publication.Bioresearch Commu. 10(2): 1495-1500, 2024 (July)